The impact of patient-held health records on continuity of care among asylum seekers in reception centres: a cluster-randomised stepped wedge trial in Germany - Straßner, Cornelia; Nöst, Stefan; Erdmann, Stella; Jahn, Rosa; Ziegler, Sandra; Wahedi, Katharina; Bozorgmehr, Kayvan (BMJ global health, 2019)
Introduction The aim of this study was to assess the effectiveness of a patient-held health record (PHR) for asylum seekers on the availability of health-related information. - Methods An explorative, cluster-randomised stepped-wedge trial with reception centres as unit of randomisation was conducted. All reception centres (n=6) in two large administrative areas in South Germany with on-site health services were included. All physicians working at these centres were invited to participate in the study. The intervention was the implementation of a PHR. The primary outcome was the prevalence of written health-related information. Secondary outcomes were the physicians’ dissatisfaction with the available written information and the prevalence of missing health-related information. All outcomes were measured at the level of patient–physician contacts by means of a standardised questionnaire, and analysed in logistic multi-level regression models. - Results We obtained data on 2308 patient–physician contacts. The presence of the PHR increased the availability of health-related information (adjusted OR (aOR), 20.3, 95% CI: 12.74 to 32.33), and tended to reduce missing essential information (aOR 0.71, 95% CI: 0.39 to 1.26) and physicians’ dissatisfaction with available information (aOR 0.5, 95% CI: 0.24 to 1.04). The availability of health-related information in the post-intervention period was higher (aOR 4.22, 95% CI: 2.64 to 6.73), missing information (aOR 0.89, 95% CI: 0.42 to 1.88) and dissatisfaction (aOR 0.43, 95% CI: 0.16 to 1.14) tended to be lower compared with the pre-intervention period. - Conclusions Healthcare planners should consider introducing PHRs in reception centres or comparable facilities. Future research should focus on the impact of PHRs on clinical outcomes and on intersectoral care. - Trial registration ISRCTN13212716. Registered 24 November 2016. Retrospectively registered. http://www.isrctn.com/ISRCTN13212716
Gesehen am 21.01.2020